Detection of bone marrow changes related to estrogen withdrawal in rats with a tabletop stray‐field NMR scanner. Issue 3 (30th September 2016) - Sarda, Yifat; Bergman, Elad; Hillel, Inbar; Binderman, Itzhak; Nevo, Uri
Abstract : Purpose: Osteoporosis is characterized by a decrease in bone mineral density (BMD). A preliminary stage of the disease is progressive bone marrow adiposity, caused by imbalance between osteogenesis and adipogenesis in the marrow. Detection of osteoporosis relies on the quantification of BMD with techniques such as dual‐energy X‐ray absorptiometry. This work aimed to detect bone marrow changes in an experimental model of osteopenia using a low‐field tabletop NMR scanner. Methods: An experiment was performed on 32 female rats, 3 months old, 16 of which were ovariectomized (OVX) and 16 were sham‐operated (sham). The femur and tibia from both hind limbs were isolated and underwent ex vivo NMR scans at four time points after the OVX and sham operations. NMR scans were complemented by BMD measurements and histology. Results: Significant changes in the bone marrow of ovariectomized rats, relative to sham operated rats, were observed after 3.5 and 4.5 months. Bone marrow adiposity was detected by significant changes in T1 and T2 relaxation times, and in the diffusion coefficient. Conclusions: This study suggests a potential detection of changes to the bone marrow using a tabletop NMR device. Clinical translation may facilitate screening, early detection of bone weakening as a result of estrogen withdrawal, and monitoring of treatment efficacy. Magn Reson Med 78:860–870, 2017. © 2016 International Society for Magnetic Resonance in Medicine.